Fecal microbiota transplantation restores gut microbiota diversity in children with active Crohn’s disease: a prospective trial - Biao Zou; Shengxuan Liu; Chen Dong; Hexiao Shen; Yongling Lv; Jiayi He; Xuesong Li; Mengling Ruan; Zhihua Huang; Sainan Shu (Journal of Translational Medicine)
Abstract Background Clinical data on oral fecal microbiota transplantation (FMT), a promising therapy for Crohn’s disease (CD), are limited. Herein, we determined the short-term safety and feasibility of FMT for pediatric patients with active CD. Methods In this open-label, parallel-group, single-center prospective trial, patients with active CD were treated with oral FMT capsules combined with partial enteral nutrition (PEN) (80%). The control group comprised pediatric patients with active CD treated with PEN (80%) and immunosuppressants. Thirty-three patients (11.6 ± 1.82 years)—17 in the capsule and 16 in the control groups—were analyzed. Data regarding the adverse events, clinical reactions, intestinal microbiome composition, and biomarker parameters were collected and compared post-treatment. Results At week 10, the clinical and endoscopic remission rates did not differ between the two groups. By week 10, the mean fecal calprotectin level, C-reactive protein level, erythrocyte sedimentation rate, simple endoscopic score for CD, and pediatric CD activity index decreased significantly in the capsule group (all P < 0.05). The main adverse event was mild-to-moderate constipation. Core functional genera, Agathobacter, Akkermansia, Roseburia, Blautia, Subdoligranulum, and Faecalibacterium, were lacking pre-treatment. Post-treatment, the implantation rates of these core functional genera increased significantly, which positively correlated with the anti-inflammatory factor, interleukin (IL)-10, and negatively correlated with the pro-inflammatory factor, IL-6. The combination of these six functional genera distinguished healthy children from those with CD (area under the curve = 0.96). Conclusions Oral FMT capsules combined with PEN (80%) could be an effective therapy for children with active CD. The six core functional genera identified here may be candidate biomarkers for identifying children with CD. Trial registration: ClinicalTrials.gov, retrospectively registered, ID# NCT05321758, NCT05321745, date of registration: 2022-04-04.